THE DEVELOPMENT OF SHARIA ECONOMIC LAW THROUGH THE PROCESS OF IJTIHAD: A LITERATURE STUDY ON THE INFLUENCE OF NATIONAL REGULATIONS AND SHARIA PRINCIPLES IN ECONOMIC ACTIVITIES IN INDONESIA - Gunawan Widjaja; Siti Nur Azizah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study examines the development of Islamic economic law in Indonesia through the process of ijtihad, with a focus on the influence of national regulations and Sharia principles in economic activities. Using a literature review method, this study examines various sources, including national regulations, fatwas from the National Sharia Council of the Indonesian Ulema Council, and rulings from Religious Courts related to Islamic economic law. The findings reveal that national regulations serve as the legal foundation providing certainty and protection for sharia economic actors, while the ijtihad process acts as a dynamic instrument enabling the adaptation of sharia law to economic developments and innovations in sharia financial products. The synergy between regulations and ijtihad forms a responsive, inclusive, and sustainable legal framework for sharia economics, thereby supporting Indonesia's position as a global centre for sharia economics.